Revisiting genetics of cleft lip with or without cleft palate and cleft palate only: a narrative review - Saiful Zaabaa, Mohamad Irsyad; Mokhtar@Makhtar, Khairani Idah; Rajion, Zainul Ahmad (Penerbit Universiti Sains Malaysia, 2023)
Cleft lip with or without cleft palate (CLP) and cleft palate only (CP) are the most common orofacial deformities observed in humans where almost 1 in 700 to 1 in 2000 babies born each year are affected worldwide. This condition occurs when the specific and independently derived facial primordial fails to fuse together, hence forming the cleft of the lip and palate or the palate alone. These orofacial abnormalities can be divided into syndromic and non-syndromic where the deformities are either associated with other disorders or present on their own, respectively. It is important to understand every step in the lip and palate development during embryonic stage to pinpoint the exact problem affecting the normal development of the human face. With current technologies, more genes are identified to be associated and caused CLP and CP in humans. Therefore, this review aimed to elaborate the latest updates on the genetics of CLP and CP. Polymorphism in some of the genes has been associated with the incidence of these anomalies. Identification of these genes provides new knowledge on how these craniofacial abnormalities occur and hopefully will enable earlier treatment of these deformities to be implemented.